Recent advances in capsule-based dry powder inhaler technology - Federico Lavorini (Multidisciplinary Respiratory Medicine, 2017)
Abstract Pulmonary drug delivery is currently the focus of accelerated research and development because of the potential to produce maximum therapeutic benefit to patients by directly targeting drug to the site of pathology in the lungs. Among the available delivery options, the dry powder inhaler (DPI) is the preferred device for the treatment of an increasingly diverse range of diseases. However, because drug delivery from a DPI involves a complex interaction between the device and the patient, the engineering development of this medical technology is proving to be a great challenge. Development of DPI systems that target the delivery of fine drug particles to the deeper airways in the lungs using a combination of improved drug formulations and enhanced delivery device technologies means that each of these factors contributes to overall performance of the aerosol system. There are a large range of devices that are currently available, or under development, for clinical use, however no individual device shows superior clinical efficacy. A major concern that is very relevant in day-to-day clinical practice is the inter- and intra-patient variability of the drug dosage delivered to the deep lungs from the inhalation devices, where the extent of variability depends on the drug formulation, the device design, and the patient’s inhalation profile. This variability may result in under-dosing of drug to the patient and potential loss of pharmacological efficacy. This article reviews recent advances in capsule-based DPI technology and the introduction of the ‘disposable’ DPI device.